2006
DOI: 10.1038/emm.2006.52
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of tilianin on the expression of inducible nitric oxide synthase in low density lipoprotein receptor deficiency mice

Abstract: We investigated the effect of tilianin upon inducible nitric oxide synthesis in the plasma of low-density lipoprotein receptor knock-out (Ldlr-/-) mice fed with high cholesterol diet and in primary peritoneal macrophages of Ldlr-/-mice. High cholesterol diet induced nitric oxide production in the plasma of Ldlr-/-mice. Tilianin reduced the level of nitric oxide (NO) in plasma from Ldlr-/-mice induced by the high cholesterol diet. Tilianin also inhibited the NO production from the primary culture of peritoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…Agastache rugosa Kuntze (Korean mint) is a perennial herb and well known as Bangah in the southern region of Korea [16]. Tilianin is a major constituent of A. rugosa and has been associated with numerous pharmacologic effects, such as antioxidant, antiatherogenic, antitumor, and antiinflammatory activities [17,18]. This plant contains flavonoids, including acacetin, tilianin, and rosmarinic acid, which contribute to these pharmacological activities [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Agastache rugosa Kuntze (Korean mint) is a perennial herb and well known as Bangah in the southern region of Korea [16]. Tilianin is a major constituent of A. rugosa and has been associated with numerous pharmacologic effects, such as antioxidant, antiatherogenic, antitumor, and antiinflammatory activities [17,18]. This plant contains flavonoids, including acacetin, tilianin, and rosmarinic acid, which contribute to these pharmacological activities [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…The novel compound KR-31378 is another potent antioxidant, ameliorating atherosclerosis in LDL receptor-deficient mice by blocking monocyte recruitment and downregulating VCAM-1 and interleukin-8 and (101). We also reported that tilianin, a major component of Agastache rugosa (Labiatae), suppresses the TNF-α-induced expression of VCAM-1 in human umbilical vein endothelial cells by inhibiting NO production via inducible nitric oxide synthase (102). However, despite numerous in vitro and animal studies, results of clinical trials evaluating the use of antioxidants (e.g., vitamin C and E, carotenoids, N-acetyl-cysteine) as chronic preventative therapy for cardiovascular diseases have been primarily negative (103).…”
Section: Antioxidant Effects and Perspectives For Atherosclerosismentioning
confidence: 99%
“…Flavonoids are well known effective natural anti-inflammatory agents (Ueda et al, 2004) that can produce antispasmodic effect as well (Yonathan et al, 2006). Studies have reported that acacetin and tilianin produce inhibition in the nitric oxide (NO) pathway to produce anti-inflammatory (Nam et al, 2006) and antihypertensive (Herná ndez-Abreu et al, 2009) responses. However, the involvement of NO in nociception has been controversial given that it is described that NO synthesis or inhibition is involved in both the reduction (Sakurada et al, 1992;Beirith et al, 2002;Caruso et al, 2005) and increase of nociceptive response (Kawabata et al, 1993;Abacioglu et al, 2000).…”
Section: Resultsmentioning
confidence: 97%